Grafiek Jaski Art Gallery Amsterdam. (Amsterdam : Jaski Art Gallery Amsterdam)
Corneille ; Brands ; Scholte, Rob ; Cremer, Jan ; Smeets, Richard ; Doucet, Jacques ; Rooskens, Anton ; Cobbaert, Jan ; Wolvecamp, Theo ; Avril, Armand ; De Groot, Annemarie ; Claus, Hugo ; Brood, Herman ; Klement, Fon
Nederlands
boek